ANALYSIS OF MARKETING STRATEGIES ON INSTAGRAM ON CONSUMERBUYING INTEREST THROUGH CUSTOMER INTERACTION AS MEDIATION - Fillah Awanis Fauzi; Erry Sunarya; Faizal Mulia Z (Journal of Economic, Bussines and Accounting (COSTING), 2026)
The increasing use of Instagram as a digital marketing platform in the food and beverage industry is not always accompanied by stable consumer engagement and purchase intention. Café Ruang Bertemu in Sukabumi City faces a similar condition, where its Instagram marketing activities have not been able to consistently drive sustainable growth in customer visits. This situation indicates problems in the effectiveness of digital marketing strategies and customer interaction in shaping consumers’ purchase intentions. This study aims to analyze the effect of Instagram-based digital marketing strategies on consumers’ purchase intention, examine the influence of customer interaction on purchase intention, and assess the mediating role of customer interaction. This research adopts a quantitative approach with a causal descriptive design. Data were collected from 98 followers of the Instagram account @ruangbertemu.smi through an online questionnaire and analyzed using Partial Least Squares–Structural Equation Modeling (SEM-PLS). The results indicate that Instagram-based digital marketing strategies have a positive and significant effect on customer interaction and consumers’ purchase intention. Customer interaction also has a positive and significant effect on purchase intention. Furthermore, customer interaction is proven to significantly mediate the relationship between digital marketing strategies and consumers’ purchase intention. The implications of this study suggest that the success of Instagram marketing is determined not only by promotional intensity but also by the quality of interaction between businesses and customers. Therefore, Cafe Ruang Bertemu and similar businesses are encouraged to develop more interactive, responsive, and consistent digital marketing strategies to enhance customer engagement and stimulate sustainable purchase intention.